A thousand years will come again. Cabot, cod, and Coaker. - Memorial University of Newfoundland. Division of Educational Technology (Memorial University of Newfoundland. Division of Educational Technology, 1985)
Looks at the history and settlement of communities on the Bonavista Peninsula (particularly Bonavista, Trinity, and Catalina). The fishery, W. F. Coaker,the establishment of the Fishermen's Protective Union of Newfoundland, and Port Union are also discussed. Hosted by Robert Pitt and featuring interviews with Dr. Gordon Handcock and Dr. J.K. Hiller from Memorial University.